FENOMENA KUALITAS LAPORAN KEUANGAN PESANTREN BERDASAR PEDOMAN AKUNTANSI PESANTREN DAN PSAK NO 45 - Solikhah, Solikhah; Sudibyo, Yudha Aryo; Susilowati, Dewi (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2019)
Islamic boarding schools are educational institutions that must be managed professionally. The phenomenon that occurs is that most non-profit organizations in Indonesia currently tend to emphasize the quality of programs and do not pay too much attention to the importance of financial management systems. This study aims to examine the quality phenomenon of Islamic boarding school financial reports based on pesantren accounting guidelines and PSAK No. 45.The method of this study is a pre-survey literature study in the form of confirmation of the availability of financial reports in Islamic boarding schools in several pesantren in Banyumas. This research proves that most of the reports presented by pesantren are financial reports that are only in the form of cash expenditure and cash receipts. Based on the results of studies of financial data and reports, it was found that most Islamic boarding schools had not applied PSAK No. 45 and the pesantren's accounting guidelines in preparing their financial statements. In conclusion, it is almost certain that there is no educational foundation that understands and uses PSAK No. 45. Accountability is therefore important because it will affect the legitimacy of boarding schools. Suggestions for further research are to do more in-depth research by looking at the phenomenon directly by emphasizing the importance of the knowledge and implementation of accounting in pesantren financial governance through accounting training in response to the phenomenon of ignorance of the quality of Islamic boarding school financial reports.